The Hidden Curriculum in Islamic Boarding Schools and Its Implications for the Formation of Santri Character: A Systematic Literature Review - Homsiyah; Tri Wahyudi Ramdhan; Moh Holil Baitaputra (Journal of Indonesian Islamic Studies, 2026)
The hidden curriculum is vital in pesantren education, often surpassing formal curricula in shaping students' moral foundations. This research synthesizes literature on its implementation and impact on character building from 2021 to 2026. Employing a Systematic Literature Review (SLR) with the PRISMA protocol, 16 final articles were selected from Google Scholar via Publish or Perish. Findings reveal that implementation manifests through four pillars: exemplary leadership (uswah hasanah), organizational culture, dormitory environment, and digital integration. Dominant traits formed include religiosity, self-reliance, discipline, and soft skills. The study highlights a shift from traditional management to digitalization, altering student interaction patterns. These implications offer a strategic framework for pesantren leaders to optimize unwritten elements, strengthening character education in the modern era.